Palliative Care Case Report: A Man with End Stage Lung Cancer with Brain Metastases - Yanuar Ardani; Hamzah Shatri; Rudi Putranto; Rendi Faris Anggono (RSUP Dr. Kariadi, 2023)
INTRODUCTION : Lung cancer accounts for 13% of malignancies in the world and the most common type of cancer suffered by men in Indonesia. The 5-year survival rate for patients with lung cancer is only 18.1%. About 25-30% will develop brain metastases. Overall palliative care is needed including biologically targeted therapy, chemotherapy, stereotactic radiosurgery (SRS), surgery in selected cases, and whole brain radiotherapy treatment (WBRT). Rare studies that take into account surgical palliation in advanced NSCLC. It has been demonstrated that metastaticectomy generally improves survival and, in some patients, even long-term survival. CASE REPORT : A 65-year-old male patient with Non-Small Cell Carcinoma favor Lung Adenocarcinoma and cerebellum metastases. The patient underwent surgery to remove a brain tumor. The patient received 8 radiotherapies and Erlotinib chemotherapy for 4 cycles for 6 months. The dose of Erlotinib 150g/24 hours was used in the first month. The dose was reduced in the 2nd to 6th month to 100g/24 hours. Assessment of palliative care was carried out using the Karnopsky Questionnaire, Fatigue Severity Scale (FSS), and Palliative Performance Scale (PPS). CONCLUSION : . Despite major improvements in the way lung cancer patients are treated in recent years, morbidity and death rates are still high. Palliative care (PC) is an approach to treating patients with life-threatening diseases, one of which is lung cancer